2018
DOI: 10.1016/bs.armc.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Human Onchocerciasis: Recent Advances Beyond Ivermectin

Abstract: The Parasite and Its Life Cycle 1.2 Clinical Presentation 2. Drugs and Drug Combinations in Clinical or Preclinical Evaluations 2.1 Diethylcarbamazine (DEC) 2.2 Ivermectin 2.3 Benzimidazole Drugs 2.4 Doxycycline 2.5 Rifampicin 2.6 Emodepside 2.7 Combination Therapy 3. Recent Advances Beyond Ivermectin 3.1 Searching for Chemodiversity within Natural Sources 3.2 The Repositioning of Closantel: Targeting OvCHT1 Chitinase 3.3 Studies on New Therapeutic O. volvus Targets 4. Methodologies for Onchocerciasis Diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…Several new promising drugs for the treatment of onchocerciasis are being tested in clinical trials [ 11 , 12 ], of which moxidectin was shown to reduce and maintain low skin microfilarial density for longer than ivermectin [ 13 ]. Macrofilaricides, currently only in an early phase of development, will be needed to drastically reduce the elimination time of onchocerciasis [ 11 , 12 ]. However, today none of these new drugs are available for mass drug administration programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Several new promising drugs for the treatment of onchocerciasis are being tested in clinical trials [ 11 , 12 ], of which moxidectin was shown to reduce and maintain low skin microfilarial density for longer than ivermectin [ 13 ]. Macrofilaricides, currently only in an early phase of development, will be needed to drastically reduce the elimination time of onchocerciasis [ 11 , 12 ]. However, today none of these new drugs are available for mass drug administration programmes.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of the protein underwent a preparation process that was performed using the Protein Preparation Wizard tool, implemented in Maestro GUI. Missing hydrogen atoms were added, missing bonds or atoms were fixed, bond orders were assigned, and water molecules were removed. The prediction of protonation states for the protein was accomplished using PROPKA, with the pH set at 7.4. The docking procedure was validated by performing a self-docking protocol and verifying the correct positing of the cocrystallized ligand. The coordinates of the bound crystallographic ligand were used as the centroid of the grid box.…”
Section: Methodsmentioning
confidence: 99%
“…PGM in mammals require the cofactor whereas PGM present in nematodes and bacteria do not [29]. The NfPGM is likely the cofactor-dependent PGM type.…”
Section: Plos Onementioning
confidence: 98%